Um desejo de eu [não] viver sem me notar: o museu como instituição pedagógica emancipatória - Castro, Diana Costa de (2012)
Museums are organizations which are passing trough a moment of crisis and, therefore, museology tries to redefine them, changing to attend a social function by means of democratizing culture. They leave behind the notion of temples and collections of objects to assume a role that modifies the structure of society and the cities, without a theory that addresses this new role. To overcome these contradictions is the new social goal of these organizations and their way of being and acting is the main motivation of this paper which aims to analyze how contemporary museums may constitute a primary locus for liberating praxis through its pedagogical character. We believe that contemporary museums may be 'someone' with whom society can count on their process of emancipation. For this, the role of these organizations should change; favoring democratic rather than economic issues and constitute themselves as a privileged space for emancipation by education. For this reason we make an adaptation of Paulo Freire's pedagogical method for museums, highlighting four main stages: the unveiling of self-knowledge and the reality from the exhibitions and research; critical thinking about the unveiled knowledge; transformation of the object into subject / praxis; exposure of the denounce or announcement of a better world. We believe that this process, strongly grounded in critical thinking and mediated by love (read as a human acting with respect and dialogue) can delimit the museum in its new role as a privileged place where part of the emancipatory process happens. However, contemporary museums may constitute a prime locus for emancipatory praxis through its pedagogical potential. It requires more than applying a method, but means to reformulate completely this organization structure and how it understands itself.